English Teachers’ Perception on The Abolition of English Subject at Elementary Schools and Its Implication for Students at SMPN 1 Langsa - Anggun Tiara Islamy (JADEs Journal of Academia in English Education, 2020)
The title of the research is “English Teacher’ Perception on the Abolition of English Subject at Elementary Schools and Its Implication for Students at SMPN 1 Langsa”. The aimed of this research were to find out English teachers’ perception on the abolishment of English subject and its implication for students’ ability in learning English at SMPN 1 Langsa. This research used qualitative method. The data were collected by using observation andsemi structuredinterview. The subject of this research were two English teachers and involving the seventh-grade students of SMPN 1 Langsa consisting of 30 students. Based on the result of research, the reseacher found that the teachers who teach English subject at Junior High School at SMPN 1 Langsa disagree with the abolishment of English subject at Elementary Schools. There were many students who had less motivation and difficulties in learning English at Junior High School level and the lesson starts from the beginning level. It can be concluded that the abolishment of English subject at Elementary school has implication on students’ ability in English subject at the seventh grade of SMPN 1 Langsa.